THE DON PRESS HISTORY: UNKNOWN PAGES (Proceedings of Southern Federal University. Philology, 2012)
Stan’ko A.I.Keywords: Don Region journalism, history, printed editions.The article analyses the causes and circumstances of insufficient research of the history of the Don Region journalism and determines the direction of future research by scientists. The author studies the first printed editions of the Don Region in the 19-th century.